The 1960s, a huge leap in Brazil and the first steps in combating illiteracy in Rio Grande (Research, Society and Development, 2018)
The aim of this paper is to analyze what made possible the development of initiatives to combat illiteracy in Rio Grande do Norte, with emphasis on the popular education movements promoted during the 1960s. This discussion is not restricted to local factors, but dialogues with the national and international context, reconstructing the scenario of popular education in the RN during the 1960s. For this purpose, we used a bibliographic review process, using classic authors in the history of education, such as Vanilda Paiva and Dermeval Saviani. others who produced works of history and memory about local popular education movements such as Moacyr de Goes and José Willington Germano. In addition to these authors, we review other academic papers that approach the theme of popular education in the RN. We could see that popular education in the RN followed the impulse of the national-developmental, was directly related to the expansion of social movements and the advance of popular governments. In addition, there was also the direct influence of groups linked to the Catholic Church. The combination of these factors enabled the emergence of popular education movements aimed at combating illiteracy. Among various movements, we highlight the activities of the Popular Culture Center (CPC) of the UNE, the Movement for Basic Education (MEB) linked to the Catholic Church, the Recife Popular Movement (MCP), the Paulo Freire 40 pm of Angicos, the Paraíba Popular Education Campaign Foundation (CEPLAR) and the Campaign "De pé no chão também se aprende a ler".